Age dependency of cerebral P-glycoprotein function in wild-type and APPPS1 mice measured with PET. Issue 1 (January 2020) - Zoufal, Viktoria; Wanek, Thomas; Krohn, Markus; Mairinger, Severin; Filip, Thomas; Sauberer, Michael; Stanek, Johann; Pekar, Thomas; Bauer, Martin; Pahnke, Jens; Langer, Oliver
P-glycoprotein (P-gp, ABCB1) is an efflux transporter at the blood–brain barrier (BBB), which mediates clearance of beta-amyloid (Aβ) from brain into blood. We used ( R )-[ 11 C]verapamil PET in combination with partial P-gp inhibition with tariquidar to measure cerebral P-gp function in a beta-amyloidosis mouse model (APPtg) and in control mice at three different ages (50, 200 and 380 days). Following tariquidar pre-treatment (4 mg/kg), whole brain-to-plasma radioactivity concentration ratios ( K p, brain ) were significantly higher in APPtg than in wild-type mice aged 50 days, pointing to decreased cerebral P-gp function. Moreover, we found an age-dependent decrease in cerebral P-gp function in both wild-type and APPtg mice of up to −50%. Alterations in P-gp function were more pronounced in Aβ-rich brain regions (hippocampus, cortex) than in a control region with negligible Aβ load (cerebellum). PET results were confirmed by immunohistochemical staining of P-gp in brain microvessels. Our results confirm previous findings of reduced P-gp function in Alzheimer's disease mouse models and show that our PET protocol possesses adequate sensitivity to measure these functional changes in vivo. Our PET protocol may find use in clinical studies to test the efficacy of drugs to induce P-gp function at the human BBB to enhance Aβ clearance.